Physical-mechanical properties of Musa acuminata particles composites (2022)
Introduction— Currently, the development of materials from renewable resources is growing worldwide; non-wood lignocellulosic fibers from different plant species or agro-industrial residues are an interesting source of raw material. Objective— The objective of this work is the development and physical-mechanical characterization of a composite material based on Musa acuminata pseudostem particles and a thermosetting resin. Methodology— The composite was prepared with particles of an average size of 450 µm, washed with a NaOH solution and oven-dried at 70 °C for 24 h. The moisture content was controlled. In manufacturing, the particles were glued with urea formaldehyde resin in a drum-type mixer and pressed in thermal plates at 160°C and 107 psi. The composites were analyzed mechanically, obtaining data on modulus of rupture, elastic modulus and tensile strength. Penetration hardness and water absorption resistance tests were also performed. Moreover, thermographic tests were performed on the surface of the material. The results were compared with those obtained in commercial composites. Results— It was observed that the Musa acuminata composite presented greater resistance to moisture absorption, higher elastic modulus and was more resistant to tensile stresses. Additionally, the commercial composite showed lower penetration resistance. The Musa acuminata composite achieved higher thermal insulation in thermographic tests. Conclusions— Musa acuminata is a species with a high agro-industrial flow and a considerable producer of residues, which has interesting viable physical-mechanical characteristics to produce particle agglomerates that meet engineering standards.